Aging in twentieth-century Britain - Greenhalgh, Charlotte, 1983- (Berkeley series in British studies, 2018)
"This book provides the first comprehensive study of the emotional, social, institutional, family, embodied and narrated lives of older people across twentieth century Britain. It demonstrates not just that older lives matter historically but also that old age is itself historically contingent and has been actively constituted in tandem with particular welfare and medical discourses. It also offers important insights into the ways in which social scientists constituted the topics of their research through their need to extrapolate from experience to abstraction, for the purposes of policy recommendation. In fact, it suggests the near impossibility of the task that social science set itself in this period: to respect individual experience while moving beyond it. Finally, the book feeds into broader historiographical discussions concerning the relationship between the 'expert' and 'experience' in this period. Returning to the data generated alongside the resulting analysis, Greenhalgh places the understandings--and lived experiences--of individuals within this broad age category center stage in a way that is both moving and intellectually enlightening"--Provided by publisher.